2023
DOI: 10.3390/polym15061534
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Alkaline Anion Exchange Membranes through Crosslinking: A Review of Synthetic Strategies and Property Relationships

Abstract: Alkaline anion exchange membranes (AAEMs) are an enabling component for next-generation electrochemical devices, including alkaline fuel cells, water and CO2 electrolyzers, and flow batteries. While commercial systems, notably fuel cells, have traditionally relied on proton-exchange membranes, hydroxide-ion conducting AAEMs hold promise as a method to reduce cost-per-device by enabling the use of non-platinum group electrodes and cell components. AAEMs have undergone significant material development over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 230 publications
(323 reference statements)
0
8
0
Order By: Relevance
“…[79] Another approach is to enhance membrane conductivity by changing the molecular structure of the polymer membrane, which includes adding flexible side chains, [80] using a polycationic group, [81] using a comb-like polymer structure, [82] adopting multi-block polymer chain, [67] and developing new cross-linked polymers. [83][84][85] Figure 6 shows the progress of the conductivity of AEMs from 2010 to date. The number of publications reporting conductivity at 80 °C has risen dramatically in recent years.…”
Section: Anion Exchange Membranementioning
confidence: 99%
“…[79] Another approach is to enhance membrane conductivity by changing the molecular structure of the polymer membrane, which includes adding flexible side chains, [80] using a polycationic group, [81] using a comb-like polymer structure, [82] adopting multi-block polymer chain, [67] and developing new cross-linked polymers. [83][84][85] Figure 6 shows the progress of the conductivity of AEMs from 2010 to date. The number of publications reporting conductivity at 80 °C has risen dramatically in recent years.…”
Section: Anion Exchange Membranementioning
confidence: 99%
“…The anion exchange resins are favored and better developed as the majority of currently established PFAS compounds are found to be anionic . The ionic characteristics of IEX are commonly gained in the production process by methylation or quaternization. , Both iodomethane and chloromethane are considered forms of methylation, depending on the designed resin structure and can result in the transfer of a cation methyl group to the resin matrix; while quaternization, on the other hand, adds a quaternary ammonium group composed of charged nitrogen atoms. Being one of the most established PFAS sorbents, the viability of IEX has been investigated in multiple trials in recent decades, with merits reported in versatility, regenerability, efficiency, and capacity.…”
Section: Interaction Mechanisms With Pfasmentioning
confidence: 99%
“…The membrane is an essential part of a wide range of electrochemical devices, such as fuel cells, flow batteries, electrolyzers, and water desalination through electrodialysis. Although renewable energy has been vigorously developed, the reliable operation of the power system faces significant challenges due to its unique interruption and instability. This situation leads to temporal and spatial gaps between the availability and consumption of energy .…”
Section: Introductionmentioning
confidence: 99%